2014
DOI: 10.1016/j.chom.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrolase of Trehalose Dimycolate Induces Nutrient Influx and Stress Sensitivity to Balance Intracellular Growth of Mycobacterium tuberculosis

Abstract: Summary Chronic tuberculosis in an immunocompetent host is a consequence of the delicately balanced growth of Mycobacterium tuberculosis (Mtb) in the face of host defense mechanisms. We identify an Mtb enzyme (TdmhMtb) that hydrolyzes the mycobacterial glycolipid trehalose dimycolate and plays a critical role in balancing the intracellular growth of the pathogen. TdmhMtb is induced under nutrient limiting conditions and remodels the Mtb envelope to increase nutrient influx, but concomitantly sensitizes Mtb to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 49 publications
4
78
0
1
Order By: Relevance
“…Thus, TDM may be one source of FM. In fact, Yang et al 22 estimated that about 20% of FM in the cell wall may be derived from the hydrolysis of TDM.…”
Section: Trehalose Dimycolatementioning
confidence: 99%
See 4 more Smart Citations
“…Thus, TDM may be one source of FM. In fact, Yang et al 22 estimated that about 20% of FM in the cell wall may be derived from the hydrolysis of TDM.…”
Section: Trehalose Dimycolatementioning
confidence: 99%
“…Among seven cutinaselike proteins with esterase activities previously described in M. tuberculosis, the authors suggested that Rv3452 is a possible TDM hydrolase in M. tuberculosis because of its closest relatedness to Msmeg_1529 21 . Indeed, it was shown later that Rv3452, and also Rv3451, share > 50% amino acid similarity with Msmeg_1529 22 . Experiments revealed that Rv3451 is the primary TDM hydrolase in M. tuberculosis 22 .…”
Section: Trehalose Dimycolatementioning
confidence: 99%
See 3 more Smart Citations